2014
DOI: 10.1177/0363546514527415
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Sexes of Bone Contusions and Meniscal Tear Patterns in Noncontact Anterior Cruciate Ligament Injuries

Abstract: No significant differences were detected between sexes with noncontact ACL injuries for location of tibial or femoral contusions or meniscal tears or for severity of medial versus lateral tibial contusions. The MRI data were not consistent with the valgus collapse mechanism of injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
72
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(84 citation statements)
references
References 40 publications
3
72
2
Order By: Relevance
“…However, in a study reporting bone bruise frequency in non-contact and contact ACL injuries, bone bruises on the medial femoral condyle and medial tibial plateau were present in 38% and 60%, respectively, of subjects with a non-contact injury mechanism 57 . Similarly, a recent study analyzing 73 subjects with non-contact ACL injury reported that 84% of males and 89% of females had MR evidence of bone bruises in both medial and lateral compartments with no differences observed between the sexes 60 . These studies 57, 60 suggest that the present study focused on a relatively common pattern of bone bruising.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…However, in a study reporting bone bruise frequency in non-contact and contact ACL injuries, bone bruises on the medial femoral condyle and medial tibial plateau were present in 38% and 60%, respectively, of subjects with a non-contact injury mechanism 57 . Similarly, a recent study analyzing 73 subjects with non-contact ACL injury reported that 84% of males and 89% of females had MR evidence of bone bruises in both medial and lateral compartments with no differences observed between the sexes 60 . These studies 57, 60 suggest that the present study focused on a relatively common pattern of bone bruising.…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, a recent study analyzing 73 subjects with non-contact ACL injury reported that 84% of males and 89% of females had MR evidence of bone bruises in both medial and lateral compartments with no differences observed between the sexes 60 . These studies 57, 60 suggest that the present study focused on a relatively common pattern of bone bruising. Future studies may investigate knee positions associated with other patterns of bone bruising.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations